2020
DOI: 10.1513/annalsats.201906-472oc
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Flavor Preference in a Cohort of Long-Term Electronic Cigarette Users

Abstract: Rationale: The use of electronic cigarettes (e-cigarettes) has rapidly increased in the United States, and thousands of e-cigarette flavors are available. However, there remains a dearth of evidence on e-cigarette flavor use patterns among older e-cigarette users. Objectives: This longitudinal study examined changes in flavor use patterns in long-term e-cigarette users, assessed self-reported adverse reactions, and evaluated users' anticipated reactions to possible U.S. Food and Drug Administration e-cigarette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 32 publications
5
30
0
Order By: Relevance
“… 26 Nontobacco flavored e-cigarettes may help enhance the relationship between satisfaction and enjoyment with vaping, as it has been reported that the use of flavors other than tobacco is associated with greater satisfaction with vaping. 24 Our study also found that satisfaction (relative to smoking) and enjoyment with vaping were greater when using candy or fruit flavors, and lower when using tobacco or unflavored e-cigarettes.…”
Section: Discussionsupporting
confidence: 65%
“… 26 Nontobacco flavored e-cigarettes may help enhance the relationship between satisfaction and enjoyment with vaping, as it has been reported that the use of flavors other than tobacco is associated with greater satisfaction with vaping. 24 Our study also found that satisfaction (relative to smoking) and enjoyment with vaping were greater when using candy or fruit flavors, and lower when using tobacco or unflavored e-cigarettes.…”
Section: Discussionsupporting
confidence: 65%
“…Our findings indicate that AEs are relatively common among e-cigarette users. In line with previous studies, mouth and throat dryness and irritation, cough, and headache were the most frequently reported AEs, particularly in our current daily e-cigarette user sample [15,[22][23][24][25][35][36][37]. The rate of AEs varies across studies with different study designs between 7-58% [15,22,24,35,36,[38][39][40].…”
Section: Discussionsupporting
confidence: 88%
“…This directive came into force on May 20 th , 2020 [54]. Numerous studies on adolescents and young adults have shown, however, that preferences for specific flavours still play an important role in consumer choices [55][56][57].…”
Section: The Hazardous Phenomenon Of Tobacco Heating Productsmentioning
confidence: 99%